MIDDLE TURBINATE PNEUMATIZATION - "CONCHA BULLOSA". A NARRATIVE LITERATURE REVIEW AND COMPREHENSIVE DEVELOPMENTAL CONCEPTS - Loredana Liliana Hurjui; Cristina Claudia Tarniceriu; Marius Constantin Moraru; Simona Alice Partene Vicoleanu; Ana Maria Haliciu; Gabriel Statescu; Razvan Radu Maxim; Alin Horatiu Nedelcu (Romanian Society of Oral Rehabilitation, 2024)
Abnormal pneumatization of the middle nasal turbinate, also named concha bullosa, is one of the most frequent anomalies of the ethmoid-osteomeatal complex. Clinical studies have demonstrated a prevalence between 14% and 53% in the general population. Apart from the high frequency, the importance of this anomaly resides in the loco-regional changes it produces. First, it modifies the airflow at the level of the nasal passages both through the mass effect and through the irritating action on the adjacent nasal mucosa. Therefore, congestion of the nasal mucosa occurs. Secondly, it is a predisposing factor for the installation of rhinosinus infections, especially with chronic rhinosinusitis and fungal sinus infections. Thirdly, concha bullosa can cause rhinogenic pain through the same irritating phenomenon at the level of the mucosa. Our paper aims to address the anatomic-clinical, diagnostic and therapeutic aspects of the pneumatization of the middle nasal turbinate, paying special attention to the concepts of development and etiological factors. Finally, yet importantly, we propose an original anatomical-morphological classification that includes semiological computer tomographic aspects highlighted both in the sagittal plane and in the axial plane.